ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM KITAB IRSYAD AL-IBAD - Nailatul Mawaddih; Rosichin Mansur; Kukuh Santoso (VICRATINA, 2021)
There are many ways and efforts that can be done so that the formation of noble character is realized. One form of effort to internalize character values before they are formed in real behavior is through reading and studying books. One of the books that can be studied to instill the value of noble character is the book of Irsyad al-'Ibad. This study is to describe the concept of the book of Irsyad al-'Ibad, describe and analyze the values of character education contained in the book of Irsyad al-'Ibad and describe the relevance of the values of character education contained in the book of Irsyad al-'Ibad with values. the value of Kemendikbud's character education. The values of character education in the book of Irsyad al-Ibad are the character values of a servant who relates to God and the relationship between fellow creatures. The components of Islamic education in the book of Irsyad al-'Ibad as the basis for learning are aqidah, ibadah and akhlak. And these values have relevance to the character values of Kemendikbud.